Adenocarcinoma originating from long-segment Barrett's esophagus over 15 cm: a series of 3 cases - Naoki Kuwayama; Isamu Hoshino; Hisashi Gunji; Toru Tonooka; Hiroaki Soda; Ryotaro Eto; Nobuhiro Takiguchi; Yoshihiro Nabeya (Surgical Case Reports)
Abstract Background Barrett's esophagus (BE) is characterized by presence of columnar epithelium in the lower esophageal mucosa, which originally comprises stratified squamous epithelium. Gastroesophageal reflux disease causes BE and BE adenocarcinoma (BEAC); further, the incidence of BEAC is increasing, especially in developed countries. Long-segment BE (LSBE) has a particularly high carcinogenic potential and necessitates treatment, surveillance, and prevention. Case presentation Herein, we report three cases of BEAC originating from LSBE larger than 15 cm. All three patients underwent surgery for the diagnosis of BEAC. A 66-year-old man with advanced esophageal cancer underwent neoadjuvant chemotherapy and subsequent subtotal esophagectomy. The postoperative pathological diagnosis was of poorly differentiated adenocarcinoma with lymph node metastasis (pT3 pN3 pM0 pStage III based on the Union for International Cancer Control TNM Classification 8th edition). Two years after the operation, the patient was diagnosed with recurrence around the celiac artery and underwent chemotherapy. An 83-year-old woman with advanced esophageal cancer underwent subtotal esophagectomy. The postoperative pathological diagnosis was of well-differentiated adenocarcinoma with supraclavicular lymph node metastasis (pT3 pN3 pM1 pStage IV). Two months after the operation, the patient was diagnosed with recurrence in the neck lymph nodes and underwent chemotherapy; however, she died. A 66-year-old man with early-stage esophageal cancer underwent subtotal esophagectomy. A superficial early cancerous lesion was seen over BE. The postoperative pathological diagnosis was of well-differentiated adenocarcinoma without lymph node metastasis (pT1a pN0 pM0 pStage 0). The patient was found to be alive and recurrence-free 3 months after the operation. Conclusions BEAC might show good prognosis if detected and treated early. Extremely LSBE is associated with a high incidence of BEAC; therefore, early detection and treatment with close surveillance is essential.